2014
DOI: 10.1017/s0033822200050347
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gaps in Tree-Ring Records: Creating a High-Resolution Dendrochronological Network for Southeastern Europe

Abstract: Dendrochronological research in North-Central Europe and the East Mediterranean has produced networks of long regional oak (Quercus sp.) reference chronologies that have been instrumental in dating, provenancing, and paleoclimate research applications. However, until now these two important tree-ring networks have not been successfully linked. Oak forests and historical/archaeological sites in southeastern Europe provide the key for linking the North-Central European and East Mediterranean tree-ring networks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In this issue, Ważny et al (2014) have demonstrated such a link through a north-south transect between Poland and northwestern Turkey.…”
Section: Pearson Ważny Kuniholm Botić Durman and Seufermentioning
confidence: 88%
“…In this issue, Ważny et al (2014) have demonstrated such a link through a north-south transect between Poland and northwestern Turkey.…”
Section: Pearson Ważny Kuniholm Botić Durman and Seufermentioning
confidence: 88%
“…A recent study noted that oak trees from Central and Eastern Europe include characteristics related to oak trees of the study area (Ważny et al, 2014). Although there are several studies for Central and Eastern Europe, (Kern et al, 2013;Čufar et al, 2014;Stajić et al, 2015), the dendroclimatological studies for oak species published that include Romania (Nechita, 2013;Nechita et al, 2017) do not include southern Romania (Vlasiei Plain), which has specific climate-related features.…”
Section: Introductionmentioning
confidence: 97%
“…Our study region is located at the transition between the Mediterranean and continental climatic influence, making it a significant area to explore crossmatching potential for linking or bridging between the major North European tree-ring chronologies and data sets from the Mediterranean. In this issue, Ważny et al (2014) have demonstrated such a link through a north-south transect between Poland and northwestern Turkey.…”
Section: Pearson Ważny Kuniholm Botić Durman and Seufermentioning
confidence: 88%